ANALISIS KONTRIBUSI DAN EFEKTIVITAS PAJAK DAERAH SEBAGAI SUMBER PENDAPATAN ASLI DAERAH (PAD) DI KOTA BITUNG - Wenur, Cindy Y.; Elim, Inggriani; Tangkuman, Steven J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Locally-generated revenue (PAD) is all income obtained locally and collected based on prevailing laws and regulations. PAD sourced by Â local taxes, local retribution, management result of separated regional wealth, and other legitimate PAD. Local taxes is a tax which collected and managed by the government and used to finance regional development. Local taxes is a potential component to increase PAD. This study aims to know how much the contribution of local taxes as a source of PAD and to know the effectiveness of local taxes in Bitung City. This study was conducted on Badan Pengelola Pajak dan Retribusi Daerah. The results show that the contribution of local taxes as a source of PAD in Bitung City during the period 2013-2017 is in good category with an average contribution 40,98% per year. The biggest contribution from street lighting tax and the lowest contribution from swallow nest tax. As for the effectiveness of local taxes during the period 2013-2017 is in very effective category with a percentage more than 100% each year.Keywords: contribution, effectiveness, local taxes, locally-generated revenue